2007
DOI: 10.1063/1.2741609
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of insulating nitride interfacial layers for germanium metal oxide semiconductor field effect transistors with high-κ oxide/tungsten nitride gate stacks

Abstract: Atomic layer deposition (ALD) was used to deposit passivating interfacial nitride layers between Ge and high-κ oxides. High-κ oxides on Ge surfaces passivated by ultrathin (1–2nm) ALD Hf3N4 or AlN layers exhibited well-behaved C-V characteristics with an equivalent oxide thickness as low as 0.8nm, no significant flatband voltage shifts, and midgap density of interface states values of 2×1012cm−1eV−1. Functional n-channel and p-channel Ge field effect transistors with nitride interlayer/high-κ oxide/metal gate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…In order to achieve high-quality Ge MOS devices, different surface passivation methods have been applied including Si passivation [410], sulfur passivation [411] metal nitride passivation [412], fluorine passivation [413], GeO x N y [414], AlO x N y [415], Y 2 O 3 , and so on. Li et al studied the HfTiO/Y 2 O 3 / Ge MOS capacitors [416].…”
Section: Ge Channelmentioning
confidence: 99%
“…In order to achieve high-quality Ge MOS devices, different surface passivation methods have been applied including Si passivation [410], sulfur passivation [411] metal nitride passivation [412], fluorine passivation [413], GeO x N y [414], AlO x N y [415], Y 2 O 3 , and so on. Li et al studied the HfTiO/Y 2 O 3 / Ge MOS capacitors [416].…”
Section: Ge Channelmentioning
confidence: 99%
“…When processed in the form of thin film, AlN finds applications as buffer layers for the growth of high quality materials [2,3], insulators for thin film transistors [4], interfacial layers for metal oxide semiconductor field effect transistors [5,6] and high-electron mobility transistors [7], surface passivation layers for surface channel field effect transistors [8] and sensitive GaAs structures [9], transparent substrates [10] and active layers [11] for extreme UV light-emitting diodes and photodetectors. AlN films are also used in the fabrication of surface acoustic wave devices [12], mechanical resonators [13], piezoelectric transducers [14], and gas sensors [15].…”
Section: Introductionmentioning
confidence: 99%
“…Different methods were studied to passivate the Ge surface, e.g. NH 3 treatment [8], atomic N surface nitridation [9], SiH 4 treatment [10], wet-NO pretreatment [11], AlN x passivation [12][13][14] and TaO x N y interlayer [7]. Also, it was reported that fluorine was a good passivant for HfO 2 / SiO 2 interface due to formation of strong Hf-F and Si-F bonds [15,16], while Xie et al [17] used F to anneal the HfO 2 in Ge MOS transistors for improved electrical properties.…”
Section: Introductionmentioning
confidence: 99%